What doesn't kill you makes you stronger: The evolution of competition and entry‐order advantages in economically turbulent contexts - Garcia‐Sanchez, Javier; Mesquita, Luiz F.; Vassolo, Roberto S. (Strategic Management Journal, 2014)
We examine the evolution of competition and entry‐order advantages in markets under macroeconomic distress. Through formal modeling of early‐mover advantages along industry life cycles subjected to economic shocks and based on simulation findings, we propose that such shocks exogenously induce temporary industry discontinuities that shift the relative value of distinct asset endowments, thereby switching the bases for competitive advantages vis‐à‐vis those found in stable contexts. A vital trade‐off then emerges between a firm's financial flexibility and its pace of investments in isolating mechanisms, such that the former operates as a contingency factor for the latter. As such, flexibility superiority boosts early‐entrants' advantages, while it alternatively gives laggards a much desired strength to out trump first‐mover rivals. Our study informs entry‐order advantage theory and management practice in economically turbulent contexts . Copyright © 2013 John Wiley & Sons, Ltd.